Industrial uses of biomass energy : the example of Brazil - Rosillo Callé, Francisco, 1945-; Bajay, Sergio V. (Sergio Valdir); Rothman, Harry, 1938- (Taylor & Francis, 2000)
This book demonstrates that energy-rich vegetation, biomass, is a key renewable energy resource for the future. However, bioenergy still faces economic, institutional and some technical barriers and these are explored in this text.